Pax3 and Pax7 interact reciprocally and regulate the expression of cadherin‐7 through inducing neuron differentiation in the developing chicken spinal cord. Issue 5 (9th September 2015) - Lin, Juntang; Wang, Congrui; Yang, Ciqing; Fu, Sulei; Redies, Christoph
ABSTRACT: Pax3 and Pax7 are closely related transcription factors that are widely expressed in the developing nervous system and somites. In the CNS, both genes are expressed in the dorsal part of the neural tube during development. Pax3 and Pax7 are involved in the sonic hedgehog (Shh) signaling pathway and are inhibited by Shh overexpression. The present study confirms in vivo that Pax3 overexpression represses the expression of Pax7, whereas Pax7 overexpression endogenously enhances and ectopically induces the expression of Pax3 in the developing chicken spinal cord. Overexpression of Pax3 and Pax7 represses the endogenous expression of cadherin‐7, a member of the cadherin family of morphogenetic genes, and induces its ectopic expression. The present study also shows that overexpression of Pax3 and Pax7 changes the fate and morphology of cells in the neuroepithelial layer and induces the expression of postmitotic neuronal markers. We show that both Pax3 and Pax7 promote the differentiation of neural progenitor cells into neurons. Furthermore, the downregulation of Pax3 and Pax7 with specific shRNAs results in apoptosis in the developing spinal cord. Collectively, these results suggest that the transcription factors Pax3 and Pax7 play important roles in regulating morphogenesis and cell differentiation in the developing spinal cord. J. Comp. Neurol. 524:940–962, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Hypothetical model for the interactions among Shh, Pax3/7, and Cdh7 in the developing spinal cord. Pax3 and Pax7 mutually regulate each other. Overexpression (+) of Pax3/7 represses endogenous expression of Cdh7 but induces its ectopic expression and neural differentiation. Inhibition (−) of Pax3/7 induces apoptosis.